(untitled) (Experimental and Applied Veterinary Research Journal, 2025)
Background: Klebsiella pneumoniae (K. pneumoniae) is an increasingly important threat to public health since the emergence of hyper virulent strains. This study aimed to evaluate the presence of hyper virulent Klebsiella pneumoniae (hvkp) in the milk and milk products. Methodology: One hundred cow’s milk and fifty local soft cheese samples from different rural areas and local markets in Baghdad city were screened. HiCrome™ Klebsiella selective agar base and indole test were used initially for bacterial identification. The isolates were also validated by Vitek®2 Compact system with the amplification of the 16S rRNA gene followed by nucleotide sequencing. Results: K. pneumoniae was totally diagnosed in thirty-three (22%) samples. PCR indicated that one (3.03%) isolate from the local soft cheese contained the K2 serotype of hvkp, together with the regulator of mucoid phenotype A (rmpA) gene and exhibited a high degree of multidrug resistance (MDR). The K2 serotype of the hvkp isolate and the rmpA gene were registered at National Center for Biotechnology Information (NCBI) under the accession numbers PX055694.1 and PX055698.1, respectively. Conclusions: The local soft cheese represents a potential source of hvkp strain; thus, there is a need to improve control and prevention strategies, particularly in the field of milk production.